Analisis Penerapan Kepmendesa PDTT Nomor 136 Tahun 2022 pada Penyusunan Laporan Keuangan BUMDes Tridaya Sakti - Namira Athaya; Tri Hesti Utaminingtyas; Nuramalia Hasanah (International Forum of Researchers and Lecturers, 2026)
Village-Owned Enterprises (BUMDes) occupy a strategic position in driving rural economic growth by managing village assets and running business activities. To strengthen accountability in financial management, the Indonesian government issued Ministerial Decree Number 136 of 2022 as the official reference for BUMDes financial reporting. Even so, a considerable number of BUMDes have yet to apply this reference fully because of constrained human resources and accounting understanding. This study sets out to examine how financial statements are prepared at BUMDes Tridaya Sakti and to put forward Excel-based reporting recommendations. A qualitative approach with a descriptive design was applied to depict the phenomenon under study. Data were gathered through interviews, observation, and documentation, then processed with the Miles and Huberman interactive model, while the recommended reporting design was built through the Analysis, Design, and Development stages of the ADDIE model. Findings reveal that financial reporting at BUMDes Tridaya Sakti is still confined to recording cash receipts and disbursements, falling short of the requirements set out in Ministerial Decree Number 136 of 2022. Accordingly, this study offers an Excel-based financial reporting model intended to support reporting that is more systematic, transparent, and accountable.